Pilot study of in-line continuous flocculation water treatment plant - Agudosi, Elochukwu Stephen; Chan, Ezzat Abdullah; Mubarak, N. M.; Khalid, Mohammad *; Pudza, Musa Yahaya; Agudosi, Ngozi Patricia; Abutu, Enemona David (Elsevier, 2018)
Human consumption of groundwater without treatment is not safe and can cause water-borne diseases and other kinds of illnesses. Usually, groundwater extracted through boreholes may be acidic and contains impurities such as organic and inorganic contaminants, microbes, and heavy metals. Hence, it becomes imperative to treat groundwater to make it potable for human consumption. This pilot study was conceptualized based on a simple and the most economical technological approach in groundwater treatment. It employed the basic concepts and working principles of essential unit operations such as coagulation, sedimentation, filtration, and adsorption to ensure potable water for human consumption based on WHO standard specifications. The plant specifically treats groundwater of pH 6.30-6.50. The average flow rate of the plant is 12,570 cm3/min (0.7542 m3/hr) and a centrifugal pump of 0.5 HP and a pipe size of 20 mm diameter were selected for this design. Equipment used were determined, sized and selected as required and the treated water quality is ensured through laboratory routine tests carried out in the course of the continuous operation of the pilot plant. Sand filter and carbon purifier are inevitable and a turbidity sensor is proposed for the filters to optimize the backwash operation. Capital cost evaluation was carried out using the percentage of delivered equipment cost method and the total capital cost for this pilot plant was estimated as One Thousand, Seven Hundred and Eighty-Two-Ringgit (RM 1,782.00 ≈ USD445.50). Thus, with this successful pilot study for a continuous treatment operation, a plant scale-up is feasible for groundwater purification to ensure potable water security in both rural and urban communities.